Emotional Intelligence Approach in Block System Arabic Learning: A Case Study at MTs NU Pakis - Alkamala, Safira Naili; Muassomah, Muassomah; Mufidah, Nuril (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The process of learning Arabic does not rely solely on students’ cognitive abilities, but is also influenced by affective aspects such as emotional intelligence. This study aims to analyze the implementation of an emotional intelligence approach in block system-based Arabic language instruction at MTs NU Pakis. The approach refers to Goleman’s five components of emotional intelligence: self-awareness, self-regulation, motivation, empathy, and social skills. The study employed a descriptive qualitative method using observation and interview techniques. The results indicate that emotional intelligence is actively integrated into the intensive three-day learning process. The teacher successfully created a conducive and interactive learning environment, facilitated students’ emotional regulation, and enhanced engagement and learning motivation. Positive social interactions between teacher and students, as well as among peers, contributed to the development of a collaborative learning atmosphere.